К вопросу о дифференциации абсолютного и относительного временного значения в форме перфекта (на материале английского и исландского языков) - Бойко, В.Г. (Kalbotyra, 1995)
The article deals with the problem of the Perfect paradigm in the modern English and Icelandic languages. The investigation shows that this grammar form has the meaning of absolute time on the paradigmatic level and that of relative time on the syntagmatic level; the formed being its invariant, the latterits variant. The realization of the variant meaning depends on the context, namely on the influence of the historic and constant Present. Unlike English, the Icelandic Perfect can be also used in the preterital meaning – the socalled distant Perfect. In this respect it bears resemblance with the Perfect in the other Scandinavian languages and especially in German.